The Impact of Campus Interaction Among Students in Enriching Student Learning Experiences in North Macedonia - Arafat Shabani; Demush Bajrami (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Researchers practicing service learning can be leaders who continuously support the teaching staff by helping them to literally understand the essence of learning through service provision, overall development of civic thought, and education in general. The potential, goals and promises of research projects based on theories of service learning are activities that lead to understanding among people, underlining here the elements such as: educating young researchers, research about teaching, the role of instruction, i.e. lectures on genuine academic teaching and overall development of participating learners; involving as many citizens as possible in higher education; establishing partnerships between university community that have their integrity. The goal of this research is to shed some light on how can higher education play an even greater role in improving the quality of life in different communities of society? In order to analyse the impact of the campus or universitystudent interaction, students of the first and fourth year have been included in the research, from all study. The results from our research proved in a convincible way that the interaction (on campus) among students from different study programs has a different impact on students themselves in terms of their co-curricular activities and their contacts among one another. However, we found out that the students who are enrolled to the Business Administration study program are more engaged into the co-curricular activities and student communication development; and the fourthyear students have more co-curricular activities, whereas first year students have more contacts among themselves.
Keywords: I23; 330; community services; campus interaction among students; enriching student learning